Intracerebral haemorrhage in young, analysis of risk factors, location, causes and overall prognosis - Kumar, Sanjeev; Janardan, Janardan (Journal of Neonatal Surgery, 2025)
Background: The subset of stroke patients between 18 and 45 known as Intracerebral Haemorrhage (ICH), it has bleeding in the brain tissue. Unlike senior people with hypertension, young people have coagulopathies, vascular malformations, trauma, and substance addiction. Understanding risk variables and how they affect haemorrhage location, causes, and prognosis is essential to improving outcomes and care in this group. Methods: This retrospective cohort study examined 110 young ICH patients identified at Indira Gandhi Institute of Medical Sciences (IGIMS) in Patna between March 2023 and June 2024. Demographic data, risk factor profiles (hypertension, substance abuse, and coagulopathies), haemorrhage sites (lobar, deep, and infratentorial), underlying causes (vascular malformations, trauma, and substance abuse), and short-term results were collected and analysed. Risk variables, haemorrhage characteristics, and patient outcomes were examined using logistic regression and chi-square testing. Results: The most common risk factors were substance abuse (27%), hypertension (36%), and coagulopathies (14%). Lobar regions (45%) and deep brain structures (30%) had the highest haemorrhages. Vascular anomalies (35%), trauma (25%), and other disorders caused most of these bleedings. Seventy percent of ICH patients had good discharge results (MRS0-2), while 15% died within six months. Early Glasgow Coma Scale score, haemorrhage volume, and intraventricular extension affected results. Conclusion: Hypertension, substance abuse, and vascular anomalies alter haemorrhage location and prognosis, making young adults more susceptible to develop ICH. Trauma and vascular anomalies caused most lobar and deep brain damage. Children with ICH face unique challenges, but timely diagnosis, individualised treatment programmes, and interdisciplinary teamwork can improve short-term outcomes. More research is needed to understand the long-term impacts and establish at-risk group management strategies.